Prediction of Student’s Major based on Grades and Psychological Test using Artificial Neural Network - Intan Yuniar Purbasari; Axvian Bagas Syah Putra (Prosiding International conference on Information Technology and Business (ICITB), 2019)
New enrolled high school students are typically grouped into majors that will determine the subjects they will take during their three-years study period. Three common majors are Life Sciences, Social Sciences, and Linguistics. Several parameters used to categorize the students are grades of certain subjects (those in the National Final Examination from the previous level) and result from a psychological test taken before enrolling in high schools. This research aims to categorize new students into three common majors based on their previous academic grades and also result from the psychological tests. Each student's preference for a certain major is also put into consideration. The accuracy of the system was 100% for the training set and 79% for the test set.Keywords: new student grouping, artificial neural network, academic grades, classification